Assessment of Immunotoxicity and Oxidative Stress Induced by Zinc Selenium/Zinc Sulphide Quantum Dots - Reshma, V. G.; Mohanan, P. V. (Frontiers in Nanotechnology, 2021)
Although ZnSe/ZnS quantum dots (QDs) have emerged as apparently less hazardous substitute to cadmium-based QDs, their toxicity has not been fully understood. Huge levels of ROS production and associated difficulties comprise the underlying reason for nanomaterial toxicity in cells. This will cause both immunotoxicity and genotoxicity. In the current work, Zinc Selenium/Zinc Sulphide (ZnSe/ZnS) QDs was synthesized, characterized and analyzed for its role in oxidative stress induction in two cell lines (HepG2 and HEK) and Swiss Albino mice. ROS production and influence of catalase activity in ROS production measured by DCFHDA assay in both HepG2 and HEK cells after exposure to ZnSe/ZnS QDs. Assessment of nitrile radical formation carried out by griess reagent. Level of GSH is assessed as a marker for oxidative stress induced by QDs. Cell death induced after exposure to ZnSe/ZnS QDs investigated by Calcein AM-PI live dead assay. Apoptotic DNA ladder assay carried out for studying the potential of ZnSe/ZnS QDs to induce DNA fragmentation. In vivo bio-nano interaction was studied by exposing Swiss Albino mice to ZnSe/ZnS QDs via i.v. and i.p. injection. Antioxidant assays were carried out in brain and liver homogenates to study the oxidative stress. LPO, GSH, GPx, GR and SOD are considered as biomarkers for the stress analysis. Blood brain barrier (BBB) integrity also studied. Spleenocytes proliferation assay was carried out to study the immunotoxicity response. ZnSe/ZnS QDs do not induce visible oxidative stress upto a concentration of 50 μg/ml. Cell death occurs at higher concentration (100 μg/ml) caused by ROS production. Overall study apparently provide attentive information that ZnSe/ZnS QDs is not capable of eliciting any serious damages to liver and brain tissues which in turn substantiates its applicability in biomedical applications.